Musical Lives: The strike of real time streaming during the Covid-19 pandemic - Odier, Felipe Saldanha; Moura, Robert; Campos, Lúcia (Revista Hipótese, 2022)
In this article, we will address the circulation and listening of amplified and recorded music, considering their audiovisual experiences and the formation of audiences for these products that touch the image of musical performances over time. From the ethnomusicological perspective, we seek to reflect on the advent of lives streaming, a phenomenon popularized during Covid-19 pandemic. From this practice of live music, in real-time streaming, we will observe its effects on musical aesthetics and sociability generated among viewers in interactive chats during performances, as well as economic incurrencies for musicians in this format. In this mode of enjoyment, we observe the presence of networks of cooperation in these social contexts, which seems to us to be indicative of conformations of contemporary musical taste.
Keywords: Musical lives; Popular song; Musical scene